PENGARUH COSTUMER RELATIONSHIP DAN COSTUMER BONDING TERHADAP LOYALITAS KONSUMEN PADA GRAPARI TELKOMSEL CABANG KEDIRI - Dian Anggraini Puspitasari; Sri Wahyuni Mega H; Lina Saptaria (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This research aims to determine the influence of customer relationships and customer bonding on consumer loyalty at Grapari Telkom Kediri branch. The variables in this research are Customer Relationship (X1), Customer Bonding (X2), and Consumer Loyalty (Y). This research uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. Meanwhile, the analysis used is validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and coefficient of determination. Sampling in this study used purposive sampling taking into consideration that there were 222 Grapari Telkom Kediri Branch patients based on the results of the research conducted. The results of this research used the SPSS 25.0 program using a significance level of 5% or 0.05 with results (1) The results of the t test calculation on the first hypothesis obtained a calculated t value of 6.527 with a significance value of 0.007 < 0.05. These results indicate that Ha is accepted and Ho is rejected, meaning that there is a partial influence between the Customer Relationship variable on Consumer Loyalty at Grapari Telkom Kediri Branch. (2) The results of the t test calculation on the second hypothesis obtained a calculated t value of 1.002 with a significance value of 0.023 < 0.05. These results show that Ha is accepted and Ho is rejected, meaning that there is a partial influence between the Customer Bonding variable on Consumer Loyalty at Grapari Telkom Kediri Branch. (3) The calculated F value in this study was 73.199 and the F significance value was 0.000, which was <0.05. It can be concluded that Ha is accepted and Ho is rejected, which means that simultaneously Customer Relationship and Customer Bonding have a significant effect on Consumer Loyalty at Grapari Telkom Kediri Branch. These results prove that empirically the third hypothesis can be proven.